2014
DOI: 10.1111/jnc.12926
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and Huntingtin protein modifications by manganese: implications for striatal medium spiny neuron pathology in manganese neurotoxicity

Abstract: High levels of manganese (Mn) exposure decreases striatal medium spiny neuron (MSN) dendritic length and spine density, but the mechanism(s) are not known. The Huntingtin (HTT) gene has been functionally linked to cortical brain-derived neurotrophic factor (BDNF) support of striatal MSNs via phosphorylation at serine 421 (S421). In Huntington's disease, pathogenic CAG-repeat expansions of HTT decrease synthesis and disrupt transport of cortical-striatal BDNF contributing to disease, and Mn is a putative enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…It is therefore possible that Mn may interact with brain-derived neurotrophic factor (BDNF), because BNDF plays a pivotal role in regulating the dendrite development and subsequent structural and functional synaptic plasticity in HDG (Alderson et al, 1990;Cohen-Cory et al, 2010;Horch and Katz, 2002;Gorski et al, 2003;Tolwani et al, 2002;Vigers et al, 2012;Wang et al, 2015). Recent studies in rodents, nonhuman primates, and human workers have also demonstrated a decreased BDNF level in the striatum, hippocampus, and plasma following Mn exposure (Liang et al, 2015;Lv et al, 2014;Stansfield et al, 2014;Sumanont et al, 2007;Zou et al, 2014). Thus, in-depth studies are necessary to further evaluate whether and to what degree Mn exposure may alter the dendritic formation in adult brain and how BDNF may contribute to Mn action.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that Mn may interact with brain-derived neurotrophic factor (BDNF), because BNDF plays a pivotal role in regulating the dendrite development and subsequent structural and functional synaptic plasticity in HDG (Alderson et al, 1990;Cohen-Cory et al, 2010;Horch and Katz, 2002;Gorski et al, 2003;Tolwani et al, 2002;Vigers et al, 2012;Wang et al, 2015). Recent studies in rodents, nonhuman primates, and human workers have also demonstrated a decreased BDNF level in the striatum, hippocampus, and plasma following Mn exposure (Liang et al, 2015;Lv et al, 2014;Stansfield et al, 2014;Sumanont et al, 2007;Zou et al, 2014). Thus, in-depth studies are necessary to further evaluate whether and to what degree Mn exposure may alter the dendritic formation in adult brain and how BDNF may contribute to Mn action.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the effects of manganese exposure with HT disease pathology, manganese exposure adversely affects medium spiny neuron dendritic length and spine density which is associated with a decrease brain-derived neurotrophic factor which caused alterations in the Htt gene which causes HT [250]. In study using a monkey model, exposure to manganese was shown to promote α-synuclein positive cells, which indicate the development of PD and dementia [251].…”
Section: Mechanisms Of Actions Of Estrogenic Endocrine Disruptors mentioning
confidence: 99%
“…Manganism is a syndrome similar to Parkinson’s disease (PD), characterized by psychiatric and cognitive deficits and motor impairment [27, 28]. Mn is also a putative environmental modifier of Huntington’s disease (HD) [2931]. The symptoms caused by the accumulation of Mn include dystonia, bradykinesia and rigidity due to damage to dopaminergic (DAergic) neurons and gliosis [12, 32].…”
Section: Introductionmentioning
confidence: 99%